(untitled) (Research, Society and Development, 2020)
Measuring Scientific Literacy allows us to evaluate how this construct can be perceived in the numerous activities that aim to promote it. The Basic Scientific Literacy Test consists of a questionnaire with great potential to measure the level of this concept. However, the literature points out research that makes use of this instrument, which was elaborated for graduates of Basic Education, in elementary school students. Thus, the problem of this study aims to analyze the psychometric characteristics of its items for this target audience, questioning whether the instrument remains valid for this group. The aim of this article is to present the results of a pilot test with 125 students, which generated the analyses to answer this question. The results highlight the discussion about the importance of ensuring the qualities of validity and reliability of the instruments when used in individuals with different school and social characteristics of those in which the questionnaire was elaborated. Its application in other samples of this population is suggested in order to verify the stability of the items and corroborate the theoretical structure of the results obtained.